eHalal4All program - promoting a halal rural products and services globally by harnessing the Network-of-Mosques(NoM) capabilities - Ahmad Dahlan, Abdul Rahman; Ahmad H.Osman, Rahmah; Ibrahim, Jamaludin; Othman, Mohd Zainudin (2014)
The population of Muslims gobally is estimated to be more than 1.6 billion, which represents about one-fifth of the world’s population. The recent religious awakening of Muslims and their realization of the importance of compliance with Shari’ah laws in business dealings have enabled them to achieve their economic and wellbeing goals. This conceptual paper proposes eHalal4All Program, which is to be adopted as one of the 1AZAM Malaysian government-sponsored programs, and implemented as a proof-of-concept in raising the economic and social status of rural communities in Sabah, Malaysia. This program has the potential to enhance wellbeing by providing these rural communities with new skills, machinery, eHalal4All Portal, network of entrepreneurs and Network-of-Mosques (NoM) in generating new sources of income. eHalal4All Program is executed based on the deployment of the Quadruple Helix Model (QHM), where a country's economic structure lies on four actors namely: Government, Academia, Industry, and Citizen, and the economic growth are generated by the clustering and concentration of talented and productive actors. Literature reviews and nine (9) blocks of Business Model Canvas (BMC) framework are used as methodology for this paper. As the extent of rural poverty in Malaysia is expected to be reduced and societal wellbeing to be enhanced through eHalal4All Program, an added benefit is the minimization of the rural-urban migration process. This in turn will result in less pressure on government to provide additional spending on services such as education, provision of clean drinking water and adequate sewage disposal, housing, and health in urban areas as well as having to deal with a host of problems associated with overgrown cities/towns such as a higher incidence of crime and of shanty towns on the outskirts of these cities. Thus, demonstrating the contribution of NoM in realising partly the meaning of “Rahmatan li’l-Alamin”.